Argentina : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Argentina's economy has rebounded strongly from the financial crisis in late 2001. Reflecting buoyant domestic demand, real GDP grew close to 9 percent in both 2003 and 2004, bringing real output level back to the peak level achieved prior to the crisis. Growth has continued in the first quarter, and consumer and business confidence indicators remain at high levels. Inflation, however, has accelerated amid rising demand, increased capacity constraints, growing wage pressures, and monetary accommodation.